Reservation Wages, Search Duration, and Accepted Wages in Europe - John T. Addison; Mário Centeno; Pedro Portugal (Institute for the Study of Labor (IZA), 2004)
This paper uses data from the European Community Household Panel, 1994-99, to investigate the arrival rate of job offers, the determinants of reservation wages, transitions out of unemployment, and accepted wages. In this exploratory treatment, we report that the arrival rate of job offers declines precipitously with jobless duration and age; that reservation wages do decline with the jobless spell (and aggregate unemployment); that transitions out of unemployment exhibit strong negative duration dependence for reasons that have more to do with the arrival rate of job offers than with reservation wages; and that the decline in reemployment wages with joblessness closely shadows the corresponding fall in reservation wages.
Keywords: J64; J65; 330; reservation wages; job offer arrival rates; unemployment duration; reemployment wages; Anspruchslohn; Arbeitsangebot; Arbeitsuche; Arbeitslosigkeit; EU-Staaten